Influence Of Farm Yard Manure And Inorganic Nitrogen Use On Growth And Yield Of Kale (Brassica Oleracea Var. Acephala) (Applied Biological Research, 2013)
An experiment was carried out in two consecutive rabi (winter) seasons of 2010 and 2011 on a silty clay loam soil to study the influence of four levels of farm yard manure FYM viz., 0, 15, 30 and 45 t ha-1and four levels of inorganic nitrogen viz., 0, 45, 90 and 135 kg ha-1on growth, yield attributes and quality of kale (Brassica oleracea L. var. acephala). Application of 45 t FYM ha-1 significantly increased growth and yield attributing characters of kale viz., plant height, plant spread, number of leaves, leaf yield plant-1, whole plant weight and leaf yield. Nitrogen @ 135 kg ha-1significantly increased all growth and yield parameters. The use of FYM @ 30 t ha-1in combination with 90 kg N ha-1 increased the growth and yield attributing characters of kale. The highest nitrogen uptake, nitrogen and protein content was recorded in kale under the treatment receiving 45 t FYM ha-1in combination with 135 kg N ha-1. Kale crop receiving 30 t FYM along with 90 kg N ha-1seemed to be the best combination in getting maximum growth and yield under temperate conditions of Kashmir.
Keywords: FYM; growth; kale; inorganic nitrogen; interaction effect; yield attributes